Marketing ensure the competitiveness of the tourism industry - Pererva, Oleksandr; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
It has been proven that tourism in its main characteristics has no fundamental differences from other forms of economic activity, therefore all the main provisions of modern marketing can be fully applied in this area. At the same time, tourism has certain features related to the nature of services provided, work, forms of sales.
Маркетингове забезпечення туристичної індустрії
Keywords: characteristics; tourism business; partners; features; factors; services